High-dose Vitamin D3 Supplementation in Children and Young Adults with HIV. Issue 2 (February 2015) - Stallings, Virginia A.; Schall, Joan I.; Hediger, Mary L.; Zemel, Babette S.; Tuluc, Florin; Dougherty, Kelly A.; Samuel, Julia L.; Rutstein, Richard M.
<x xml:space="preserve">Abstract</x> Background: Suboptimal vitamin D status is prevalent in HIV-infected patients and associated with increased risk of disease severity and morbidity. We aimed to determine 12-month safety and efficacy of daily 7000 IU vitamin D3 (vitD3) versus placebo to sustain increased serum 25-hydroxyvitamin D (25(OH)D) and improve immune status in HIV-infected subjects. Methods: This was a double-blind trial of perinatally acquired HIV (PHIV)-infected subjects or behaviorally acquired HIV (BHIV)-infected subjects (5.0-24.9 years). Safety, 25(OH)D-related parameters and immune status were assessed at baseline, 3, 6 and 12 months. Results: Fifty-eight subjects enrolled (67% male, 85% African American and 64% BHIV) and 50 completed with no safety concerns. In unadjusted analyses, there were no differences between randomization groups at baseline; at 3, 6 and 12 months, 25(OH)D was higher with supplementation than baseline and higher than with placebo (P < 0.05). In adjusted mixed models, in the supplementation group, the fixed effect of 25(OH)D was higher (P < 0.001). Percentage of naive T-helper cells (Th naive%) were significantly (P < 0.01) and T-helper cells (CD4%) marginally (P < 0.10) increased with supplementation in those taking highly active antiretroviral therapy (HAART), and RNA viral load was reduced (P ⩽ 0.05). In exploratory linear models, change in 25(OH)D predicted RNA viral load at 3 and 12 months and CD4% at 3 months (P < 0.05). Conclusions: Daily 7000 IU vitD3 for 12 months was safe in HIV-infected subjects and effective in increasing 25(OH)D. Supplementation improved some clinically important HIV immune markers in subjects on HAART. Adjunct therapy with high-dose, daily vitD3 for HIV-infected subjects and for those on/off HAART requires further investigation.